Pengaruh Pemberian Gadget Pada Perkembangan Anak Usia Dini Di Desa Penarungan - Suyanti, Ni Wayan; Suarnaya, I Putu (Cetta: Jurnal Ilmu Pendidikan, 2021)
In today's modern era, almost everyone in various circles from young to old is inseparable from using gadgets. Gadgets as electronic devices that can make it easier for everyone to find and get information anywhere and anytime. Gadgets are also one of the communication tools that can connect a person from various countries easily. Behind the advantages of using gadgets, there is also another side that can affect early childhood development. The importance of early childhood education which aims to avoid unwanted things to children from an early age needs to be considered. This research uses a type of qualitative research using a descriptive analysis approach. The results of this study indicate that appropriate stimulation and experiences in childhood have a positive impact on children's learning abilities, health, and well-being as adults. The overuse of gadgets in early childhood is quite a concern nowadays because it can have a negative impact on the child's developmental system and can even be slow to respond when someone interacts with the child. Therefore, it is important to focus on the overall development of children from an early age and ensure that gadget use does not hinder their development. Each child has different needs, so it is important to monitor and adjust the use of equipment according to the child's development and needs.